In vitro antibacterial and cytotoxic activities of carvacrol and terpinen-4-ol against biofilm formation on titanium implant surfaces - Maquera-Huacho, Patricia Milagros [UNESP]; Tonon, Caroline Coradi [UNESP]; Correia, Marilia Ferreira [UNESP]; Francisconi, Renata Serignoli [UNESP]; Bordini, Ester Alves Ferreira [UNESP]; Marcantonio, Élcio [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP] (Taylor & Francis, 2018)
This study evaluated the antibacterial properties of carvacrol and terpinen-4-ol against Porphyromonas gingivalis and Fusobacterium nucleatum and its cytotoxic effects on fibroblast cells. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were examined. The minimum biofilm inhibition concentration (MBIC) was evaluated by XTT assay. Biofilm decontamination on titanium surfaces was quantified (CFU ml−1), evaluated by confocal laser scanning microscopy (CLSM) and cytotoxic activity by MTT. The MIC and MBC for carvacrol were 0.007% and 0.002% for P. gingivalis and F. nucleatum, and 0.06% for terpinen-4-ol for both microorganisms. The MBIC for carvacrol was 0.03% and 0.06% for P. gingivalis and F. nucleatum, and for terpinen-4-ol was 0.06% and 0.24%. The results indicated anti-biofilm activity using carvacrol (0.26%, 0.06%) and terpinen-4-ol (0.95%, 0.24%) and showed cytotoxic activity similar to chlorohexidine (CHX). However, terpinen-4-ol (0.24%) showed higher cell viability than other treatments. Carvacrol and terpinen-4-ol showed antibacterial activity in respect of reducing biofilms. Moreover, CHX-like cytotoxicity was observed.
Keywords: antibacterial activity; biofilm; Carvacrol; cytotoxic activity; peri-implantitis; terpinen-4-ol